Parental and Teacher Collaboration in Internalizing Religious Values to Foster Students’ Worship Discipline in Islamic Schools - Kholis, Nur; Ahmadi (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the collaboration between parents and teachers in the internalization of religious values to foster students’ worship discipline at MTs Negeri 3 Jember, Indonesia. The study specifically examines the roles of parents and teachers, communication strategies, and the supporting and inhibiting factors influencing the process of religious value internalization in Islamic schools. This research employed a qualitative descriptive approach conducted at MTs Negeri 3 Jember. Data were collected through in-depth interviews, participant observation, and documentation analysis involving 26 participants consisting of Islamic Religious Education teachers, homeroom teachers, students, and parents selected through purposive sampling techniques. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings revealed that the internalization of religious values was implemented through four major strategies: exemplary behavior, religious habituation, supervision, and collaborative communication between family and school. Teachers strengthened worship discipline through structured religious programs such as congregational shalat dhuha, shalat dhuhur, and Qur’anic recitation, while parents reinforced religious practices through worship habituation at home, supervision of prayer times, and smartphone usage control. The study also found that family–school collaboration had a greater influence on students’ worship discipline than previously assumed. The novelty of this study lies in its emphasis on integrated collaboration between parents and teachers in fostering worship discipline through communication, supervision, and religious habituation simultaneously. This study contributes to the discourse on Islamic character education by offering an integrative perspective on religious value internalization within contemporary Islamic educational settings.